Bone Augmentation Procedures in a Patient with Acromegaly - Laura Andreea Schiller; Albert Cristian Schiller; Adalbert Schiller; Aida Gabriela Dascalu; Silviu Brad (Case Reports in Dentistry, 2020)
The objective of this clinical case is to evaluate if bone augmentation procedures can be successful in a patient with altered bone metabolism due to a systemic disease: acromegaly. Two guided bone regeneration procedures were made on the same patient: horizontal ridge augmentation with lateral wall approach sinus graft of the left maxilla and horizontal ridge augmentation of the front left maxilla. CBCT assessment of the new formed bone was made after a minimum of nine months and dental implants were placed. The results show that bone augmentation procedures can be successful in a patient with acromegaly, after pituitary adenoma removal, when autologous bone is not included in the grafting procedure.